Diagnosing and managing spinal injury in patients with ankylosing spondylitis - Waldman, S; Brown, C; Lopez de Heredia, L; Hughes, R (Elsevier, 2013)
BACKGROUND: Individuals with ankylosing spondylitis are at an increased risk of vertebral fractures. These are often unstable, leading to primary and secondary neurological injury and conferring high levels of morbidity and mortality. Fractures in these patients can occur after minimal trauma and are easily missed, with potentially disastrous consequences. OBJECTIVES: To educate health professionals who may be involved in the initial assessment and management of ankylosing spondylitis patients with possible spinal injuries, despite not being spinal specialists. CASE REPORTS: We present three cases from our own hospital, which illustrate the pitfalls associated with traumatic spinal injury in ankylosing spondylitis. Case 1 shows why delayed presentation of spinal injury is common, as well as demonstrating the need for multiple imaging modalities in some patients. Case 2 is an example of primary neurological injury in this patient group, and case 3 highlights the risk of secondary neurological injury, as well as the effect of multiple comorbidities on patient outcomes. CONCLUSIONS: It is important that staff in the Emergency Department have an understanding of the extreme caution that is needed in the management of possible spinal injuries in patients with or suspected of having ankylosing spondylitis.